2017
DOI: 10.1177/000313481708301217
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial Comparing Low Density versus High Density Meshes in Patients with Bilateral Inguinal Hernia

Abstract: We present a randomized clinical trial to compare postoperative pain, complications, feeling of a foreign body, and recurrence between heavyweight and lightweight meshes in patients with bilateral groin hernia. Sixty-seven patients with bilateral hernia were included in our study. In each patient, the side of the lightweight mesh was decided by random numbers table. Pain score was measured by visual analogue scale, on 1st, 3rd, 5th, and 7th postoperative day, and one year after the surgery. There were no stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…One study used a polyester mesh (13) while the remaining 47 studies used meshes made of polypropylene. Nine of the studies used two meshes (48)(49)(50)(51)(52)(53)(54)(55)(56), resulting in 48 studies mentioning mesh weight for 57 meshes. Of these 58 meshes, 26 were by the authors defined as lightweight meshes (9-28, 50-55), 30 as heavyweight meshes , and one as a mediumweight mesh (56).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study used a polyester mesh (13) while the remaining 47 studies used meshes made of polypropylene. Nine of the studies used two meshes (48)(49)(50)(51)(52)(53)(54)(55)(56), resulting in 48 studies mentioning mesh weight for 57 meshes. Of these 58 meshes, 26 were by the authors defined as lightweight meshes (9-28, 50-55), 30 as heavyweight meshes , and one as a mediumweight mesh (56).…”
Section: Resultsmentioning
confidence: 99%
“…The pore size was reported in 13 studies (9-11, 14, 18, 20, 22, 23, 28, 50-53) (Figure 2B). Two studies described that the lightweight mesh had large pore size without specifying the size in mm (10,22), while the remaining ten studies either reported the pore diameter in mm or in µm, which was converted to mm (one study informed the size by email ( 23)) (9,11,14,18,20,23,(50)(51)(52)(53). Two studies had unspecified pore sizes (9,53) and two studies used a range (14,28).…”
Section: Lightweight Meshmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 However, Carro et al showed that no significant difference was between lightweight and heavyweight groups in terms of chronic pain. 23 In the study comparing TCM and PM, Koch et al showed that chronic pain was less in patients with TCM than in patients with PM. 6 Similar to previous studies, we observed lower chronic pain using TCM compared to PM.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations have demonstrated that patients using lightweight meshes present less foreign body sensation and discomfort after inguinal herniorrhaphy than those with heavy weight meshes. Regarding acute and chronic pain, a survey by Carro et al revealed that there were remarkable differences in pain degree on the first and seventh days postoperatively. Lightweight meshes can effectively alleviate short-term pain.…”
Section: Strategies For Reducing Postoperative Complicationsmentioning
confidence: 99%